2020
DOI: 10.4081/mrm.2020.692
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A virus H1N1 associated pneumonia - acute and late aspects evaluated with tomography high resolution in hospitalized patients

Abstract: Background: Influenza A (H1N1) virus often compromises the respiratory tract, leading to pneumonia, which is the principal cause of death in these patients. The purpose of this study was to review the acute and late phase pulmonary findings in influenza A(H1N1) associated pneumonia using high resolution computed tomography (HRCT), and to determine the importance of performing end expiration series. Methods: Between July and August 2009, 140 patients presented with influenza A (H1N1) confirmed by real-timepolym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Air trapping was depicted in three critical patients, among whom one patient had multiple pneumatoceles in bilateral lung and right hydropneumothorax during treatment. Cristina et al 21 reported that the appearance of air trapping was due to airway obstruction which was an essential factor in patients with dyspnea. Furthermore, we found that pulmonary parenchyma involvement was more common than airway involvement in both severe and critical patients, which may be related to the fact that the H1N1 virus is more likely to involve the alveolar rather than the bronchiolar epithelium 16 …”
Section: Discussionmentioning
confidence: 99%
“…Air trapping was depicted in three critical patients, among whom one patient had multiple pneumatoceles in bilateral lung and right hydropneumothorax during treatment. Cristina et al 21 reported that the appearance of air trapping was due to airway obstruction which was an essential factor in patients with dyspnea. Furthermore, we found that pulmonary parenchyma involvement was more common than airway involvement in both severe and critical patients, which may be related to the fact that the H1N1 virus is more likely to involve the alveolar rather than the bronchiolar epithelium 16 …”
Section: Discussionmentioning
confidence: 99%